Smoking prevalence and its impacts on lung cancer mortality in Sub-Saharan Africa: an epidemiological study - Winkler, Volker; Ott, Jördis J.; Cowan, Melanie; Becher, Heiko (Preventive medicine, 2013)
Background - Reliable mortality data are sparse for developing countries. Furthermore, risk factor prevalence information is hardly available and thus not taken into consideration when estimating mortality. - Methods - The authors used a validated, statistical model combined with representative smoking prevalence from WHO STEPS surveys to estimate lung cancer mortality for six Sub-Saharan African countries (Benin, Malawi, Mozambique, Niger, Sierra Leone, Swaziland). Results were compared to a reference database (GLOBOCAN). Using different smoking prevalence scenarios, future lung cancer deaths were estimated. - Results - The prevalence of current moderate smoking among males ranged from 8.7% to 34.6%. Prevalence was much lower among females. For all countries considered, our mortality estimates were higher than GLOBOCAN estimates that do not consider prevalence: Overall, we estimated 2405 lung cancer deaths for 2008 compared to 531 deaths estimated by GLOBOCAN. Up to 2030, lung cancer deaths are expected to increase in general and by over 100% in Benin and Niger. Even under the assumption of decrease in smoking prevalence, lung cancer mortality will rise. - Conclusion - On the bases of detailed smoking prevalence information, our findings implicate a higher lung cancer burden in low income countries. The epidemiologic transition in African low-income countries alludes to the need for targeted health prevention efforts.